Polish lustration and the models of transitional justice - Krotoszyński, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
Transitional justice in the post-communist countries of Eastern Europe concentrates on the problem of the lustration of former secret service officers and their clandestine collaborators and on the question of access to files created by the communist political police. The aim of the article is to present the Polish experience in this field in view of the theoretical framework available in transitional justice literature. Thus, the text begins with definitions of some basic notions connected with dealing with the past. The article also proposes three basic models of transitional justice. The third part offers an account of Polish lustration and public disclosure measures and assigns those instruments to the models of transitional justice. The final section presents some concluding remarks on the evolution of Polish lustration.